Ethical principles in the use of health databases for research - Herrera-Añazco, Percy (2023)
The generation of multiple personal and health data occurs within various processes related to health care services, health surveillance, scientific research, among others. These data can serve as sources of information for monitoring indicators related to individual and community health conditions, as well as for conducting research that can be used for health decision-making and the generation of public policies. However, it is necessary that the use of these health databases be under strict methodological and ethical parameters, so, in this article, we analyze general and methodological aspects of the use of health databases for research. We also identify the benefits, risks, ethical concerns, and recommendations for the appropriate use of health databases.